Equality in Process: Community Land Dispute Resolution Mechanisms in Kenyan Law - Witchger, Kathryn E. (Columbia Journal of Gender and Law, 2018)
In 2010, Kenya ratified a Constitution that formalized its traditional dispute resolution mechanisms (“TDRMs”). In 2016, the legislature extended TDRM formalization to community land through the Community Land Act. While these mechanisms give greater voice to communities, they are implemented through local leaders, usually limited to male elders, and do not adequately represent marginalized groups. During a typical land dispute, it is the elders that resolve the matter because they have the respect of the community, and the best memory for the boundaries of the land. They will call a “baraza” or gathering in which community members will have a chance to voice their opinions and furnish relevant evidence before the elders make a decision. In practice, this means that the new laws run the risk of formalizing not only TDRMs, but also unequal participation in these important mechanisms. While this Note focuses on the gendered impact of TDRMs, disparate access to TDRMs has a particular impact on unmarried women, youth, and other marginalized groups. The formalization of TDRMs is important because land is crucial to Kenyans: it is “not merely a factor of production; it is first and foremost, the medium which defines and binds together social and spiritual relations within and across generations.”